Antibacterial and hemostatic performance of chitosan–organic rectorite/alginate composite sponge. Issue 62 (8th July 2015) - Zhang, Honghui; Lv, Xiaoxing; Zhang, Xinping; Wang, Hongjun; Deng, Hongbing; Li, Yuejun; Xu, Xiaoli; Huang, Rong; Li, Xueyong
<x xml:space="preserve">Abstract</x> We fabricate a novel chitosan–OREC/SA composite sponge and study the antibacterial and hemostatic performances.